Zoom: Jesse Marlow – the unexpected is just around the corner - United Nations Educational, Scientific; Cultural Organization (The UNESCO Courier, 2025)
Anything Can Happen and Probably Will – it would be hard to find a better title for Australian photographer Jesse Marlow’s series of images gleaned from his wanderings around Melbourne and Sydney. Indeed, each image is the beginning of a story, a sketch to be continued from the viewer’s imagination. A distracted passer-by, a few leaves stranded on the pavement, a silhouette bent over by the wind – all turn the city into a short-lived stage-set, where the incongruous vies with the poetic for a place.